Deadly Echoes - Mehl, Nancy (Bloomington, Minnesota Bethany House Publishers, 2015)
"In the small town of Sanctuary, Missouri, Sarah has finally found a peace absent from her childhood as an orphan; when her sister suddenly reappears---only to disappear again---can Deputy Sheriff Paul Gleason help solve the mystery that's still haunting her?"--
Keywords: Missing persons -- Fiction; Christian fiction; Mystery fiction